Mesenteric CD103+DCs Initiate Switched Coxsackievirus B3 VP1-Specific IgA Response to Intranasal Chitosan-DNA Vaccine Through Secreting BAFF/IL-6 and Promoting Th17/Tfh Differentiation - Zhao, Haoxin; Yang, Jie; Qian, Qian; Wu, Manli; Li, Min; Xu, Wei (Frontiers in Immunology, 2018)
Intranasal Chitosan-formulated DNA vaccination promotes IgA secretion in the intestine. However, the mechanism whereby chitosan-DNA skews IgA class switch recombination (CSR) of B cells in the Gut-associated lymph tissue (GALT) is not fully resolved. In this study, we investigated the effects of nasally administered chitosan-DNA (pcDNA3.1-VP1 plasmid encoding VP1 capsid protein of Coxsackievirus B3) on IgA production, DC activation and Tfh/Th17 response in the intestine. Compared to DNA immunization, intranasal chitosan-DNA vaccination induced antigen-specific IgA production in feces, a pronounced switching of antigen-specific IgA+ plasmablast B cells in the mesenteric lymph nodes (MLNs) and an enhanced expression of post-recombination Iα-CH transcripts/ IgA germline transcript (αGT) as well as activation-induced cytidine deaminase (AID) in MLN B cells. MLN Tfh frequency was markedly enhanced by chitosan-DNA, and was associated with VP1-specific IgA titer. 24 hrs after immunization, intranasal chitosan-DNA induced a recruitment of CD103+DCs into the MLN that paralleled a selective loss of CD103+DCs in the lamina propria (LP). In vivo activated MLN-derived CD103+DCs produced high levels of IL-6 and BAFF in response to chitosan-DNA, which up-regulated transmembrane activator and CAML interactor (TACI) expression on MLN B cells. Upon co-culture with IgM+B in the presence of chitosan-DNA, MLN CD103+DCs induced IgA production in a T-dependent manner; and this IgA-promoting effect of CD103+DC was blocked by targeting TACI and, to a lower extent, by blocking IL-6. MLN CD103+DCs displayed an enhanced capacity to induce an enhanced CD4+Th17 response in vivo and in vitro, and IL-17A deficient mice had a pronounced reduction of specific intestinal IgA following immunization. Taken together, mesenteric CD103+DCs are indispensable for the adjuvant activity of chitosan in enhancing DNA vaccine-specific IgA switching in gut through activating BAFF-TACI and IL-6-IL-6R signaling, and through inducing Th17/Tfh differentiation in the MLN.